Site-selective remote C(sp3)–H heteroarylation of amides via organic photoredox catalysis - Hui Chen (Nature Portfolio, 2019)
Nitrogen-centered radicals are valuable intermediates for the controllable and selective functionalization of remote inert C(sp3)–H bonds. Here, the authors report an amidyl radical-triggered, metal-free and site-selective C(sp3)–H heteroarylation of amides under photoredox conditions.